Lutheranism, anti-Judaism, and Bach's St. John Passion : with an annotated literal translation of the libretto - Marissen, Michael (Oxford University Press, 1998)
Bach's St. John Passion is surely one of the monuments of Western music, yet performances have become inevitably controversial. In large part, this is the result of the combination of powerful, highly emotional music coupled with a text that includes passages from a gospel marked by vehement anti-Judaic sentiments. What did this masterpiece mean in Bach's day, and what does it mean today? Although the bibliographies on Bach and on Judaism have grown enormously since World War II, there has been very little work on the relationships between these two areas. This is hardly surprising; writers focusing on issues of anti-Semitism often lack musical training and are, in any event, interested in more pressing social and political issues. Bach scholars, on the other hand, have mostly concentrated on narrowly defined musical topics. And strangely, almost no scholarly attention has been given to the relationships between Lutheranism and Judaism as they affect the St. John Passion. Through a reappraisal of Bach's work and its contexts, Michael Marissen confronts Bach and Judaism directly, providing interpretive commentary that could serve as a basis for more informed and sensitive discussions of this troubling work.